Inflammation and Cardiovascular Risk: Investigating the Link between CRP and Coronary Artery Disease - Khan, Farhat Ullah; Musa, Muhammad; Bibi, Ayesha; Iqbal, Mohsin; Khan, Muhammad Idrees (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the association between C-reactive protein levels and the severity of coronary artery disease in a population of patients. Methodology: This was a retrospective observational study involving 220 patients, divided into two groups based on their hs-CRP levels: Group A (<3 mg/L) and Group B (≥3 mg/L). Data was collected from hospital records, including patient demographics, CRP levels, and coronary angiography results. Chi-square and T-tests were used for statistical analysis, with p < 0.05 considered significant. Results: Of the 220 patients, Group B (hs-CRP ≥3 mg/L) was significantly older (55.1 ± 9.4 years vs. 50.2 ± 11.1 years, p = 0.0004). Chi-square test showed a significant correlation between CRP levels and CAD severity (χ² = 15.21, p = 0.0016), with more patients in Group B presenting with multi-vessel disease (TVD/DVD). T-test for age comparison between CRP groups revealed a significant age difference (t = -3.59, p = 0.0004). Conclusion: Elevated CRP levels are strongly associated with increased CAD severity and older age in patients, supporting CRP as an effective inflammatory marker for predicting cardiovascular risk. These findings highlight the importance of incorporating CRP testing into routine cardiovascular screening.